Effect of biological control against generalist pests (insect and mite) on egg plant (solanum melongеna) field - Z, Altantsesteg; J, Oyungerel; D, Undarmaa (Mongolian Journal of Agricultural Sciences, 2019)
We conducted this study on the “Black Beauty” variety from Russia, which was planted in a 120 sqrm greenhouse in the Agropark Center of the Mongolian University of Life Sciences in 2017. During vegetation period of egg plant were occurred the polyphagous insect pests such as two spotted spider mite (Tetranychus urticae), тrips (Thripidaes.sp), peach aphid (Myzodes persicae) and caused a injury at 1-2 rate. For controlling these arthropod pests, we have used 4 different treatments as А-(predatory mites- Phytoseilus persimilis, Amblyseius swirskii) ), B- (Neem oil), C- (Predators+Nеем oil), D-BEB (LC) 2% as comparing to control plot. In calculating the effectiveness of treatments, А-(predatory mites- Phytoseilus persimilis, Amblyseius swirskii) -79.1%, B- (Neem oil)-73.7%, C- (Predators+Nеем oil)-85.5%, D-BEB (LC) 2% -83.1% as comparing to control plot were killed respectively. We have tested 4 different treatment including the predacious mite (Phytoseiulus persimilis) to control a two spotted spider mite (TSSM)-Tetranychus urticae) and A.swirskii against trips on the eggplant field . The treatments have been included A (predatory mite alone at 1:5 ratio), B (P+N (predatory mite at 1:5 ratio+Neem oil), C-neem oil alone), LC+BEB 2% and control plots with 4 replications. We have assessed the efficacy of each control treatment, and the B ( predatory mite+neem oil) treatment has reduced TSSM densities at most. These treatments for controlling the pests was increased the eggplant yield 3.8-36.4% per sqm area comparing to control plots. There was observed a differences between yield of control and treatment plots and observed as A plots (t=2.19, d.f.=174, p≥0,29), B plots (t=0.88, d.f.=174, p≥0,37),C plots (t=8.8, d.f.=174, p≥3.78) as shown on the result of T-test analysis of SPSS. Цэсийн (solanum melongеna) талбайд тархсан үе хөлтөн хөнөөлт организм (шавж, хачиг), тэдгээртэй тэмцэх биологийн аргын үр нөлөөг судалсан дүн Хураангуй: Бид энэхүү судалгааны ажлыг 2017 онд ХААИС-ийн Агропарк Сургалт, судалгааны төв дэх 120 мкв нийлэг хальсан хүлэмжинд тариалсан цэсийн ОХУ-ын “Чёрная красавица” сорт дээр гүйцэтгэв. Ургамал ургалтын хугацаанд цэсийн талбайд хоёр толбот шүлхий хачиг(Tetranychus urticae), трипс (Thripidaes.sp), Тоорийн бөөс (Myzodes persicae) зэрэг үе хөлтний хүрээний хөнөөлтэй, элдэв идэшт зүйлүүд давхцан гарч бүлгээр хөнөөл учруулж байсан бөгөөд эдгээрийн эсрэг тэмцэх аргын А-(Ангуучин хачгууд- Phytoseilus persimilis, Amblyseius swirskii) ), B - (неем тос), C- (Ангуучин+Nеем тос), D-BEB (LC) 2% зэрэг хувилбаруудыг хяналттай (E) харьцуулан туршиж, үр дүнг тогтоолоо. Эдгээрээс тархалт, хөнөөлийн хувьд трипс, хоёр толбот шүлхий хачиг нь зонхилон тархаж, цэсийн навчийг 1-2 баллаар гэмтээж байв. Туршилтанд хэрэглэсэн хувилбаруудаас А. Ангуучин фитосейлюс хачиг \1:5\ хувилбар 79.1%, B. Neem тос /0.01% уусмал + Фитосейулус хачиг /1:5/ -85.5% буюу хамгийн өндөр , C. Neem тос /0.01% уусмал/-73.7%, D. BEB (LC) 2% уусмал /Дархлааны бэлдмэл/ 83.1% -иар хөнөөлт организмыг үхүүлсэн техник үр дүнг үзүүлэв.Тэмцэх аргын хувилбаруудын ургац хяналтын дэвсгээс давсан бөгөөд A,B,C,D хувилбаруудын ургац 23.69- 29.66 kг-аар хяналтын(E)-аас илүү байгааг SPSS, T-test-ийн аргаар шинжилэхэд A хувилбар (t=2.19, d.f.=174, p≥0,29), B хувилбар (t=0.88, d.f.=174, p≥0,37),C хувилбар (t=8.8, d.f.=174, p≥3.78) байгаа нь хувилбаруудын ургац хяналтын хувилбараас бодит зөрүүтэйг харуулж байна. Түлхүүр үг: Хүлэмж, шүлхий хачиг, ангуучин хачиг, биологийн хамгаалал